Adapting and Testing the Indonesian Version of the Psychometric Properties of the Cognitive Flexibility Inventory (CFI) Measuring Tool - Rahayu, Maria Nugraheni Mardi; Aprodita, Nindya Putri; Rasyida, Afinnisa (Indigenous, 2022)
Abstract. Cognitive flexibility is an important mental ability to facilitate cognitive restructured learning. This ability can be used as a benchmark for an individual's adaptive function in dealing with life changes. This study aims to examine the psychometric properties of the Cognitive Flexibility Inventory (CFI) developed by Dennis and Vander Wal (2010), which was adapted into Indonesian language. The CFI measuring instrument consists of 20 items with 2 factors, namely the Alternatives and Control factors. Tests were carried out using Exploratory Factor Analysis and Confirmatory Factor Analysis. This study involved 1250 early adult individuals in Indonesia (mean age=24.71 years) who were divided into two groups of samples randomly for exploratory analysis (n=300) and confirmatory analysis (n=950). The results of the analysis show that the two-factors structure of the 15 CFI items in the Indonesian version has psychometric properties that are acceptable fit. These results shows that the Indonesian version of CFI can be used for research or assessment tool for various cognitive therapies. For future research it is recommended to conduct a concurrent validity testing for the Indonesian version of CFI.Keywords: cognitive flexibility inventory Indonesian version; confirmatory factor analysis; exploratory factor analysis.